Latent of The Victims: Perlakuan Terhadap Anak Paska Mengalami Kekerasan Seksual - Henky Fernando; Yuniar Galuh Larasati; Agus Indiyanto; Riky Novarizal; Syahrul Akmal Latif (Endogami: Jurnal Ilmiah Kajian Antropologi, 2023)
The treatments of children after experiencing sexual violence from their social structure does little to make children become victims again in the process of resilience. Studies that have discussed this context have only focused on handling the victim's condition, so they have not comprehensively explained the treatment received by the victim. This study focuses on the question "How is the treatment received by children after experiencing sexual violence by their social structure?" To answer this question, this study uses a qualitative descriptive approach in exploring cases of sexual violence against minors through online media coverage. The process of reading the news is focused on news titles that contain cases, victims, and the treatment received by children after experiencing sexual violence. Important findings in this study show that children after experiencing sexual violence often experience intimidation, discrimination, and decisions that are counterproductive to their social structure, such as the family, community, and school authorities. Based on these findings it is possible to formulate a concept of Latent of the victims as a contribution to this study. This study also recommends the importance of comparing cases, victims, and treatment received by children after experiencing sexual violence by interviewing groups of girls and boys who are macro and more empirical.